Analysis Of Company Performance Using The Balanced Scorecard Method (Case Study At Pt Pln Indonesia Power Unit Bisnis Pem-bangkitan Saguling) - Fadya, Zayana; Roekhudin (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2026)
This study aims to analyze and evaluate the performance of PT PLN Indonesia Power Unit Bisnis Pembangkitan (UBP) Saguling using the Balanced Scorecard approach. The research employs a case study method with a descriptive-comparative analysis. The data used in this study consists of performance measurement results from the company over the 2021–2023 period. The findings indicate that the Balanced Scorecard applied to performance measurement has been adapted to include five new perspectives: financial and market, customer, product and process effectiveness, workforce focus, leadership, governance, and corporate social responsibility. This approach differs from the original Balanced Scorecard concept. However, aligning the Balanced Scorecard with the company’s strategic plan has enabled a more comprehensive assessment of performance. The analysis results show that PT PLN Indonesia Power UBP Saguling has achieved a “Platinum” or “Outstanding” rating in its performance evaluation, reflecting the effectiveness of the Balanced Scorecard implementation within the company.